Effects of training on the development of footballers agility - Božic, D.; Kricka, O. (Sportski Logos, 2021)
The aim of the systematic review was to determine the effects of training on the development of football agility based on the collected data and analyzed papers published in scientific and professional articles between 2009 and 2018. The electronic databases used in the creation of the review paper are the following: ResearchGate, Google Scholar, PubMed Scopus and SCI. Papers were selected based on several criteria: type of study, results, age group. The results of the research showed that the plyometric training method is most often used for the development of agility. Some research has shown us that agility can also be developed by combining plyometric training with some other training (dynamic stretching, strength exercises). In addition to plyometric training, proprioceptive training and SAQ training (a combination of strength training, endurance and football technique) are increasingly used to developt agility.